Astigmatisma miop simplek yang mengalami ambliopia pada anak sekolah dasar di Yogyakarta - Wasisdi Gunawan (Berita Kedokteran Masyarakat (BKM), 2006)
Purpose: To report the astigmatism in elementary schoolchildren and determine the relationship between simple myopia astigmatism and amblyopia.Design: Population- based cross sectional studyMethods: Snellen chart, Crowding test, Neutral Density Filter Test and Autorefraktometer were used. Setting: Elementary School inspection covering 13 sub districts in region Yogyakarta.Population: In all, 1082 student elementary schoolchildren with refractive errors, aged 5 to 14 year, 177 eyes with amblyopia, 647 eyes with the astigmatism (correctable more than 0,25 D, cylindrical (+)or (- )), and 114 eyes with the simple myopia astigmatism. Results: Astigmatism were found in 647 eyes (29.89%), simple myopia astigmatism: 114 eyes, astigmatism eyes with amblyopia: 67 (8,98%), and simple myopia astigmatism eyes with amblyopia. Astigmatism myop simplex is not significantly influence the happening of amblyopia (p=0,869). The angle of the astigmatic axis strongly relates to the risk of developing amblyopia. Axes Â± 15 degrees from the main axes did not affect the risk of amblyopia but oblique astigmatism significantly increases the risk of developing amblyopia (p= 0.000). There are no significant association between refractive power of simple myopia astigmatism and the risk of developing amblyopia (p=0,907)Conclusions: Eyes with simple myopia astigmatism with amblyopia were reported. Simple myopia astigmatism is not significantly related to amblyopia, but the angle of the astigmatism axis is related to the development of amblyopia. Keywords: child amblyopia; simple myopia astigmatism